Use of Internet and Electronic Resources among Medical Professionals with Special Reference to Tamil Nadu: A Case Study - Thanuskodi, S. (Journal of Information and Knowledge, 2012)
Today, the advent of information technology has resulted in reducing the size of libraries. In fact, these smaller modern libraries are rich potential of information. This has been possible due to the digitization of information. The digital and electronic information is based on digitized data/information, which has gradually replaced paper-based records. The internet is also making substantial inroads in patient care and dissemination of health care information. It is changing the way health sciences professionals obtain information. They use the internet and electronic resources to do things like accessing medical records, providing remote patient care through telemedicine facilities, and accessing health care literature. Medicine is among many other sciences, an area in which the expansion of information is enormous and which is critically dependent on up to date information. These factors have influenced the implementation of problem based learning approach in the medical education. Numerous search tools are available to locate appropriate sources and without these search tools, the chance of finding relevant information on the Web would be slim. Even with the help of search tools, users must be able to use sophisticated searching techniques and strategies of respective search tools in order to find relevant information. Results of the present study show that less than 2 hours of access to internet takes the first order reporting among the medical professionals of Tamil Nadu. 2-3 hours of access to internet the second, 3-4 hours of access to internet the third, 4-5 hours of access to internet the fourth and above 5 hours of access to internet the last. Study reveals that respondents have high problems in accessing e-resources in terms of virus, difficulty in using digital resources due to lack of IT knowledge and limited access to computers. The respondents have moderate problems in accessing relevant information and taking long time to view. The respondents have least problems towards slow accessibility, lack of time and too much information retrieved.